OPTIMALISASI MODUL PEMBELAJARAN BERBASIS PROYEK DALAM PENINGKATAN PEMAHAMAN KONSEP FISIKA DI SMPN 4 METRO - Ira Yulita; Intan Sovi Aghnia Qolbi; Iche Widdia Putri; Arif Rahman Aththibby; Friska Octavia Rosa (Universitas Muhammadiyah Metro, 2024)
Physics education at the junior high school level is often faced withdifficulties in approaching students with abstract concepts. Project-basedlearning modules are considered a contextual and relevant approach toeveryday life, allowing students to learn actively through project activities. Thisresearch uses the natural observation method involving physics teachers andstudents of SMPN 4 Metro. The natural observation method in itsimplementation uses observation sheet instruments and interview sheets.This article optimizes the concept of optimizing the project-based learningmodule which is used as an effective strategy in helping understand conceptsin physics learning at SMPN 4 Metro. The results of the literature review showthat students' understanding of physics concepts will increase and beeffective if physics learning uses project-based modules. This needs to beoptimized in its application to learning as a learning resource. So there is aneed for further studies and research regarding the effectiveness andimplementation of modules and projects in physics learning.